Analysis of Impact of Selected Microeconomic Characteristics on Bank Capital Structure. Empirical Evidence from Poland in the Years 2013-2019 - Wiktoria SŁOMIANY1; Marcin KĘDZIOR2 (Communications of International Proceedings, 2021)
The article analyzes the debt structure of Polish listed banks. The most important determinants of making decisions regarding the capital structure are described and the most important theories of capital structure are highlighted. The level of development of the Polish banking sector in the context of other countries in the region was presented. The following factors influencing the capital structure were subject to empirical verification: liquidity, bank size, profitability, dividends, assets tangibility, revenue diversification. Empirical materials were analyzed on the basis of descriptive statistics and correlation analysis.
Keywords: Capital Structure; Liquidity; Profitability; Poland; Czechia